Phytochemical characterization and pharmacological evaluation of aerial and root parts of Dalea pazensis Rusby [Fabaceae] - Peralta, Mariana Andrea; Bedoya Aguirre, Einy Nallybe; Negro, Melisa Fabiana; Echeverría, Javier; Santi, Maria Daniela; Ortega, Maria Gabriela (Frontiers in Pharmacology, 2026)
BackgroundThe Dalea genus [Fabaceae] is rich in bioactive flavonoids and contains underexplored species, such as Dalea pazensis Rusby, with potential for antifungal and dermatological applications.PurposeConsidering the limited knowledge available on D. pazensis, this study aims to expand the current understanding of its chemical and biological potential.Material and MethodsSequential extraction of D. pazensis roots was performed using solvents of increasing polarity. Additionally, essential oil (EO) was obtained from the aerial parts. Extracts and EO were chemically characterized by ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) and gas chromatography/mass spectrometry (GC-MS), respectively. Antifungal activity was evaluated against azole-sensitive and azole-resistant Candida albicans strains, while tyrosinase inhibition was assessed in the different extracts using an in vitro enzymatic assay.Results and discussionThe chloroform extract (CDp) exhibited the most potent antifungal activity (minimum inhibitory concentration, MIC = 125 μg/mL), a relevant value considering that the reference drug fluconazole shows an MIC of 32 μg/mL in this resistant strain, underscoring the extract’s significant activity despite azole resistance. CDp showed significant tyrosinase inhibition (half-maximal inhibitory concentration, IC50 = 1.27 μg/mL). UPLC-MS/MS analysis identified (2S)-5,7,2′,4′-tetrahydroxy-5′-(1‴,1‴-dimethylallyl)-8-prenylflavanone (compound 1) as the major constituent, previously linked to antifungal activity and efflux pump inhibition. EO analysis revealed β-caryophyllene (41.1%) as the main component, suggesting a distinct chemotype within the species.ConclusionThis is the first chemical report of the EO and the deepening of prenylflavonoid content in different extracts of D. pazensis, highlighting the pharmacological relevance of its dual antifungal and antityrosinase profile, a combination of interest for dermatological formulations targeting fungal infections, hyperpigmentation, or post-infectious dyschromias. The findings underscore this species as a promising source of prenylated flavanones with dual antifungal and anti-tyrosinase activity, as well as bioactive volatiles with antifungal activity. The results support its use in developing natural antifungal therapies, particularly against MDR pathogens.